2016
DOI: 10.5624/isd.2016.46.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the anterior loop of the mandibular canal: A study using cone-beam computed tomography

Abstract: PurposeSufficient area in the interforaminal region is required for dental implant placement, and the anterior loop of the mandibular canal is located within the limits of this area. The aim of this study was to evaluate the prevalence and extent of the anterior loop in a Brazilian sample population using cone-beam computed tomography (CBCT).Materials and MethodsCBCT images from 250 patients (500 hemimandibles) obtained for various clinical indications were randomly selected and evaluated to determine the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 15 publications
1
34
0
2
Order By: Relevance
“…In this study, we found no significant differences in the length of MF between the sexes. There was also no significant difference in the size of MF between the age groups in this study, as in some recent studies [ 13 , 22 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, we found no significant differences in the length of MF between the sexes. There was also no significant difference in the size of MF between the age groups in this study, as in some recent studies [ 13 , 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…We found a significant difference between the sexes (13.1 mm in men and 11.9 mm in women), but not between the age groups. Previous studies have reported that the MF was located 13.2 mm above the lower border of the mandible, with significant sex differences (men tended to have higher values than women) [ 13 , 15 , 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported the importance of various neurovascular anatomic structures identified on cross‐sectional imaging, including: 1) inferior alveolar (mandibular) canal; 2) anterior loop and mandibular incisive canal; 3) mental foramen; 4) lingual canal; and 5) maxillary incisive/nasopalatine canal, and highlight the variability of imaging identification and characteristics of these structures in relation to implant placement 98‐109 . Hence, efforts are underway to automate identification of the mandibular canal 110 …”
Section: Resultsmentioning
confidence: 99%
“…Different studies have reported the importance of various neurovascular anatomic structures identified on cross-sectional imaging, including: 1) inferior alveolar (mandibular) canal; 2) anterior loop and mandibular incisive canal; 3) mental foramen; 4) lingual canal; and 5) maxillary incisive/nasopalatine canal, and highlight the variability of imaging identification and characteristics of these structures in relation to implant placement. [98][99][100][101][102][103][104][105][106][107][108][109] Hence, efforts are underway to automate identification of the mandibular canal. 110 In addition, the use of CBCT has been found to be effective in locating blood vessels in the lateral wall of the maxillary sinus, which should be appreciated prior to sinus augmentation procedures.…”
Section: Use Of Cbct For Anatomic Characterizationmentioning
confidence: 99%
“…In this study, we assessed anterior loop variants on CBCT images (Types A, B, and C), as previously described by Li et al [ 17 ] and Do Nascimento et al [ 18 ]. We found a higher prevalence of the anterior loop (Type A) and the lowest prevalence of Type B.…”
Section: Discussionmentioning
confidence: 99%